Nonparametric tests of the unbiasedness of Olympic figure skating judgements - Campbell, B.; Galbraith, J. W. (The Statistician, 1996)
We use recently developed nonparametric tests for orthogonality to test the null hypothesis of an absence of national bias in the judging of Olympic figure-skating events. The results, and accompanying parametric estimates, offer strong evidence of a small bias which changes little across time. There is also some evidence that the bias is more marked for skaters who are medal contenders than for less strong competitors.